A draft genome assembly for the eastern fox squirrel, Sciurus niger. Issue 12 (22nd September 2021) - Kang, Lin; Michalak, Pawel; Hallerman, Eric; Moncrief, Nancy D
Abstract: The eastern fox squirrel, Sciurus niger, exhibits marked geographic variation in size and coat color, is a model organism for studies of behavior and ecology, and a potential model for investigating physiological solutions to human porphyrias. We assembled a genome using Illumina HiSeq, PacBio SMRT, and Oxford Nanopore MinION sequencing platforms. Together, the sequencing data resulted in a draft genome of 2.99 Gb, containing 32, 830 scaffolds with an average size of 90.9 Kb and N50 of 183.8 Kb. Genome completeness was estimated to be 93.78%. A total of 24, 443 protein-encoding genes were predicted from the assembly and 23, 079 (94.42%) were annotated. Repeat elements comprised an estimated 38.49% of the genome, with the majority being LINEs (13.92%), SINEs (6.04%), and LTR elements. The topology of the species tree reconstructed using maximum-likelihood phylogenetic analysis was congruent with those of previous studies. This genome assembly can prove useful for comparative studies of genome structure and function in this rapidly diversifying lineage of mammals, for studies of population genomics and adaptation, and for biomedical research. Predicted amino acid sequence alignments for genes affecting heme biosynthesis, color vision, and hibernation showed point mutations and indels that may affect protein function and ecological adaptation.